The mid-term results of minimal medial epicondylectomy and decompression for cubital tunnel syndrome - (:unkn) unknown (My University, 2004)
OBJECTIVES: We evaluated the mid-term follow-up results of patients who were treated by minimal epicondylectomy and decompression for cubital tunnel syndrome. METHODS: The study included 17 elbows of 15 patients (9 females, 6 males; mean age 45 years; range 35 to 63 years) who underwent minimal medial epicondylectomy and in situ decompression for cubital tunnel syndrome, which was diagnosed through history, physical examination, and electrodiagnostic tests. Before surgery, all the patients received various conservative treatments for at least six months, with no beneficial effect. Thirteen patients had unilateral, two patients had bilateral involvement, with 11 elbows on the dominant side. The mean duration of symptoms was 14 months (range 3 to 36 months). Preoperative grading of nerve compression according to the McGowan system was as follows: three patients (20%) grade I, 11 patients (73.3%) grade II, and one patient (6.7%) grade III. The results of surgical treatment was evaluated according to the Wilson-Krout criteria. The mean follow-up was 32 months (range 25 to 64 months). RESULTS: Symptomatic improvement was achieved in all the patients. The results were excellent in 11 elbows (64.7%), good in five elbows (29.4%), and fair in one elbow (5.9%). None of the patients developed ulnar nerve palsy or subluxation, medial elbow instability, or weakness of the flexor-pronator origin. Pain and tenderness detected at the osteotomy site in four elbows disappeared after a mean of three months. CONCLUSION: Minimal medial epicondylectomy and decompression was found to be a safe and effective method with a low complication rate in the treatment of cubital tunnel syndrome.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Male; Range of Motion, Articular; Decompression, Surgical; Cubital Tunnel Syndrome